2014
DOI: 10.1179/2046905514y.0000000166
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive ventilation with bubble CPAP is feasible and improves respiratory physiology in hospitalised Malawian children with acute respiratory failure

Abstract: Background In low-income countries and those with a high prevalence of HIV, respiratory failure is a common cause of death in children. However, the role of non-invasive ventilation with bubble continuous positive airway pressure (bCPAP) in these patients is not well established. Methods A prospective observational study of bCPAP was undertaken between July and September 2012 in 77 Malawian children aged 1 week to 14 years with progressive acute respiratory failure despite oxygen and antimicrobial therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…In a low-resource setting, with limited monitoring, we determined a priori that we would limit bCPAP pressures to pressures safely used in previously reported observational studies. 16 17 Notably, two blinded paediatric intensivists independently reviewed this protocol and agreed with this approach prior to study implementation. Future work could examine whether higher bCPAP pressures are feasible, effective and safe in routine care settings with limited supervision and safety measures.…”
Section: Discussionmentioning
confidence: 99%
“…In a low-resource setting, with limited monitoring, we determined a priori that we would limit bCPAP pressures to pressures safely used in previously reported observational studies. 16 17 Notably, two blinded paediatric intensivists independently reviewed this protocol and agreed with this approach prior to study implementation. Future work could examine whether higher bCPAP pressures are feasible, effective and safe in routine care settings with limited supervision and safety measures.…”
Section: Discussionmentioning
confidence: 99%
“…Walk et al 2 describe an observational study of bubble CPAP in 77 Malawian children aged 1 week to 14 years; they conclude that it can be implemented in an African hospital with high-risk patients and limited resources and is well accepted by staff and patients. Similarly, McAdams et al 3 describe the successful implementation of bubble CPAP in a rural Ugandan neonatal unit.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized controlled trials were identified in children looking at the use of continuous positive airway pressure (CPAP) in children in resource-limited settings [110,111]. There were three observational studies [112][113][114] and a systematic review primarily looking at neonates [109].…”
Section: Noninvasive Ventilation For Children With Acute Respiratory mentioning
confidence: 99%
“…A randomized controlled trial in Ghana compared early CPAP for children with respiratory distress to delayed CPAP, documenting an improvement in the primary outcome of improved respiratory rate [111]. Two observational study in Malawi reported both improved respiratory physiology with the use of bubble CPAP in children up to age 14 years and a 70% survival in all children treated with bubble CPAP, with a strong ease of use reported [112,114]. An observational study in India reported a decreased rate of need for intubation, compared with children started on nasal prong oxygen [113].…”
Section: Noninvasive Ventilation For Children With Acute Respiratory mentioning
confidence: 99%